Research on social media marketing in museums ——a case study on the Asian Civilisations Museum - Huang, Da (Nanyang Technological University, 2022)
Social media is more than a virtual space where information is announced. For museums, it is a useful tool which can be exploited in many ways to support the sharing of culture and the visitor experience of museums. Despite the benefits, the majority of museums are not implementing effective strategies to promote their educational and cultural services on social media platforms. This paper is concerned with the social media strategies of museums and the marketing purposes they serve, focusing on a case analysis of the Asian Civilisations Museum (ACM), which held a successful GuoPei exhibition in 2019. After an opening summary of the wider literature on the meanings and functions of social media marketing, this paper discussed the GuoPei exhibition and assessed its subject matter within the framework of the broader agendas at work. It also affords insights into the significance of social media platforms and their particular importance in attracting and communicating with the audience of museums. The findings of the case analysis revealed that ACM effectively utilized the influence of celebrities to disseminate information on exhibitions to a wider audience. In addition, the director of ACM also played a significant role by using social media to inspire his followers with his personal enthusiasm for the museum exhibits. However, ACM should improve on collaborating its social media identity across their different platforms and pay more attention to facilitating interaction with its online users. The results of this study contributes to the management of social media marketing in museums, and future research in this field should continue to explore methods that would allow museums to build and manage relationships with their visitors more efficiently